Correction: Tuan, D.A. Leveraging Climate Data for Dengue Forecasting in Ba Ria Vung Tau Province, Vietnam: An Advanced Machine Learning Approach. Trop. Med. Infect. Dis. 2024, 9, 250 - Dang Anh Tuan (Tropical Medicine and Infectious Disease)
Following the initial publication [...]